2018
DOI: 10.1158/1535-7163.mct-18-0234
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Inhibitor Enhances the Antitumor Effect of PARP Inhibitor in Breast Cancer Cells by Modulating DNA Damage Response

Abstract: The androgen receptor (AR) is expressed in 60%-70% of breast cancers regardless of estrogen receptor status, and has been proposed as a therapeutic target in breast cancers that retain AR. In this study, the authors aimed to investigate a new treatment strategy using a novel AR inhibitor AZD3514 in breast cancer. AZD3514 alone had a minimal antiproliferative effect on most breast cancer cell lines irrespective of AR expression level, but it downregulated the expressions of DNA damage response (DDR) molecules, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…AR was demonstrated to protect prostate cancer cells from DNA damage in vitro [29,30]. AR was also shown to maintain production of DNA damage response molecules in some breast cancer cells and it prevents the accumulation of damaged DNA in vitro [31]. Recent investigations have demonstrated that high AR expression was significantly associated with worse local recurrence-free survival after radiation therapy, which is known to induce DNA damage, and AR can be as a mediator of radioresistance in triple negative breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…AR was demonstrated to protect prostate cancer cells from DNA damage in vitro [29,30]. AR was also shown to maintain production of DNA damage response molecules in some breast cancer cells and it prevents the accumulation of damaged DNA in vitro [31]. Recent investigations have demonstrated that high AR expression was significantly associated with worse local recurrence-free survival after radiation therapy, which is known to induce DNA damage, and AR can be as a mediator of radioresistance in triple negative breast cancer [32].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in this study, the patient in case 1 who had rapid progression was AR positive and likely represented a luminal androgen receptor (LAR) subtype of breast cancer, rather than the basal subtype that dominates TNBC. AR expression in breast cancer has been shown to limit effects of PARPi in preclinical models and may explain the indifference of the tumor in case 1 to PARP inhibition (Li et al, 2017, Min et al, 2018, Luo et al, 2016). Both the MEDIOLA and TOPACIO trials demonstrated activity of PARP and ICB in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, preclinical models have identified a number of potential PARPi combinations, some of which have been evaluated in early phase clinical trials (Fang et al, 2018, Fang et al, 2019, Ibrahim et al, 2012, Jiao et al, 2017, Juvekar et al, 2012, Konstantinopoulos et al, 2019, Labrie et al, 2019b, Li et al, 2017, Liu et al, 2013, Matulonis et al, 2017, Min et al, 2018, Shen et al, 2019, Sun et al, 2017, Sun et al, 2018, Vena et al, 2018, Wang et al, 2019, Yin et al, 2017). However, responses, while encouraging in a subset of patients, remain limited in depth and duration.…”
Section: Discussionmentioning
confidence: 99%
“…Nkx3.1 was initially found as an androgen regulated homeobox gene located mainly in the prostate, and was extensively studied as a tumor suppressor in prostate cancer (23,24). Multiple studies, however, have since linked it to other tissue types and downregulation to their associated malignancies including the breast, oral mucosa, and liver (25)(26)(27)(28). There is scarce literature describing Nkx3.1 expression specifically in the bladder.…”
Section: Discussionmentioning
confidence: 99%